Co-production in climate services for the electricity sector in Brazil – Insights from the CLIMAX project - Jean C.H. Miguel; Renzo R. Taddei; Marley C.L. Moscati; Caio A.S. Coelho; Iracema F.A. Cavalcanti; Luiz F. Rezende; Celso von Randow (Climate Services)
This research paper presents the findings and lessons from the international CLIMAX project—Climate Services Through Knowledge Co-production: A Euro-South American Initiative for Strengthening Societal Adaptation Response to Extreme Events. The project, engaging with the Brazilian National Electric System Operator (ONS), explores co-production as a method to implement climate services in the context of Brazil, particularly within the country’s hydroelectric power sector. Through interactive research and transdisciplinary collaboration, the CLIMAX project evaluates both the implementation of climate services and the concept of utility in knowledge co-production. The research identifies inherent diversity and “utility paradoxes” within the co-production process. These paradoxes involve the perceived relevance of climate information versus its integration into systems, and its instrumental use versus its justification for decisions. The study highlights the significance of stakeholder engagement, close and meaningful communication, and adaptability to context-specific needs. By sharing experiences from a five-year interactive research initiative, it offers insights into improving practices for future co-production endeavors. This entails recognizing varied research contexts, managing co-design processes with an awareness of time and resources, and encouraging flexibility and personal transformation within co-design.